Social Network Site Appearance Comparison's Prediction of Anxiety Among Chinese Females: The Mediation Effect of Body Area Satisfaction, Overweight Preoccupation, and Self-Esteem - Hai, Ri; Yang, Yin (Frontiers in Psychiatry, 2022)
Social network site appearance comparison refers to a tendency of compare the body image of oneself to others when using the social network sites. It was found to be associated with negative emotions, e.g. depression, among young females, and this association was mediated by body image and self-esteem. However, researches on the chain mediating role of body image and self-esteem in anxiety had been limited. Therefore, the current study examined the chain mediating role between social network site comparison and anxiety among 320 Chinese females, using Social Network Site Appearance Comparison Scale (SNSACS), Multidimensional Body-self Relations Questionnaire (MBSRQ), Self-esteem Scale (SES) and the anxiety subscale of Depression-Anxiety-Stress Scales (DASS). Results revealed that, (1) SNSACS, SES, and DASS anxiety scores were significantly correlated with each other, and the scores of two MBSRQ subscale, i.e. body areas satisfaction and overweight preoccupation, were significantly correlated with SNSACS, SES, and DASS anxiety scores; (2) Body Areas Satisfaction and self-esteem played a chain mediating role in the effect of social network site appearance comparison on anxiety; (3) Overweight Preoccupation and self-esteem played a chain mediating role in the effect of social network site appearance comparison on anxiety. The findings may inspire new ideas for understanding how social comparison triggers anxiety, and develop methods to reduce anxiety derived from appearance comparison among Chinese females.